Investigating The Neglected Safety Practices Influencing Safety Performance Of Building Construction Projects In Sindh Province Of Pakistan - Muhammad Tarique Lakhiara Lakhiara; Abd Halid Abdullah; Muhammad Tahir Lakhiar (NAROTAMA UNIVERSITY, Indonesia, 2021)
Safety non-performance has not only contributed to higher levels of injuries but also decreased total productivity in the building sector. Through improving standards of safety practices, the condition can be changed. This paper provides a framework for recognizing the most neglected safety practices that must be improved. The research was performed using a questionnaire survey of 33 safety practices. Data obtained through 210 questionnaires from respondents who were working on building projects in the Sindh Province were analyzed using statistical package for the social sciences. All safety practices have been prioritized based on their mean safety performance values. Statistics have shown that the average safety performance of the building industry is 60.596 per cent. Construction safety practices that need special attention are listed as; (a) People should work safely even when they are not being supervised (b) Safety training provided to the employees of subcontractors (c) Investigations carried out to identify the causes of accidents (d) Accidents are reported/recorded (e) throwing or dropping of material/equipment carelessly. The findings also have shown that the factor 'Accident reporting and investigation mechanism', has the lowest level of safety performance, accompanied by 'Workers' involvement', 'Safety training', 'Safety practices', 'Safety meetings. The findings of this report will provide building stakeholders with valuable knowledge for safe work practices.